Incidence of anterior cruciate ligament injuries among elite ballet and modern dancers - Liederbach, M.; Dilgen, F. E.; Rose, D. J. (The American Journal of Sports Medicine, 2008)
Ballet and modern dance are jump-intensive activities, but little is known about the incidence of anterior cruciate ligament (ACL) injuries among dancers.